Construction of Islamic Education Orientation from the Pesantren Perspective: Teun A. van Dijk's Critical Discourse Analysis of Tebuireng Magazine for the 2015–2025 Period - Imam Mukti, Adiansyah; Rosyidin, Muhammad Abror (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2026)
Pesantren are challenged to preserve their Islamic identity while responding to modernity, scientific development, and technological transformation. This study analyzes the construction of Islamic education orientation, curriculum integration, students' moral values, and its development in Tebuireng Magazine from 2015 to 2025. Using a qualitative literature study and Teun A. van Dijk's Critical Discourse Analysis, the study examines twelve articles from the Main Presentation column through the dimensions of text structure, social cognition, and social context. The findings show that Tebuireng Magazine constructs Islamic education as an integrative paradigm that combines pesantren traditions with modern demands through Ahlussunnah wal Jamaah, classical Islamic texts, scholarly sanad, science, technology, and leadership. Curriculum integration encompasses religious knowledge, science, technology, character education, leadership, and students' moral development. The discourse evolved through three phases: institutional identity consolidation (2015–2018), epistemic defense (2019–2021), and pedagogical-technocratic transformation (2024–2025). The study concludes that Tebuireng Magazine functions as an ideological medium that promotes integrative, adaptive, and transdisciplinary pesantren-based education and provides a reflective reference for contemporary pesantren curriculum development.